Intimate partner violence against women with intellectual disability: A relational framework for inclusive, trauma‐informed social services. (30th July 2022) - McConnell, David; Phelan, Shanon K.
Abstract: Women with intellectual disability experience intimate partner violence at higher rates and tend to remain in abusive relationships longer than non‐disabled women. The purpose of this inquiry was to generate a preliminary set of principles and delineate domains of support as a general guide for social service workers supporting women with intellectual disability through the difficult, often stop‐start process of ending an abusive relationship and creating a desired future. Taking a pragmatic inquiry approach, guiding principles and domains of support were generated through a triangulated engagement with relational theory, relevant published research, and original data gathered through interviews with five experienced social service workers. The results comprise a relational framework for inclusive, trauma‐informed services aimed at fostering the relational autonomy of women with intellectual disability. Enacting relational principles of reflexivity, recognition, solidarity and safety, social service workers can support women with intellectual disability with safety planning, securing basic life needs, strengthening social relationships, acquiring new skills and nurturing self‐affective attitudes of self‐respect, self‐efficacy and self‐esteem.